2021
DOI: 10.3171/2020.11.spine201565
|View full text |Cite
|
Sign up to set email alerts
|

The utility of supine radiographs in the assessment of thoracic flexibility and risk of proximal junctional kyphosis

Abstract: OBJECTIVE Supine radiographs have successfully been used for preoperative planning of lumbar deformity corrections. However, they have not been used to assess thoracic flexibility, which has recently garnered attention as a potential contributor to proximal junctional kyphosis (PJK). The purpose of this study was to compare supine to standing radiographs to assess thoracic flexibility and to determine whether thoracic flexibility is associated with PJK. METHODS A retrospective study was conducted of a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Similarly, there was no significant difference of preoperative TK and GTK between the PJK group and the non-PJK group in our study. Therefore, evaluation of thoracic spine has been extended to not only the magnitude of kyphotic angle but also thoracic flexibility, [26][27][28] thoracic distribution, 22,29,30 and thoracic inclination. 31,32 Reciprocal changes of thoracic shape in degenerative lumbar deformity remain understudied.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there was no significant difference of preoperative TK and GTK between the PJK group and the non-PJK group in our study. Therefore, evaluation of thoracic spine has been extended to not only the magnitude of kyphotic angle but also thoracic flexibility, [26][27][28] thoracic distribution, 22,29,30 and thoracic inclination. 31,32 Reciprocal changes of thoracic shape in degenerative lumbar deformity remain understudied.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that some of those who underwent revision may have been aligned outside this range, possibly leading to mechanical complications or poor clinical outcomes. 16,17 Understanding the initial alignment of patients who go on to revision may require a more nuanced assessment, including intraoperative and predischarge radiographs, especially considering that the majority of junctional kyphosis occurs before the first postoperative follow-up. [18][19][20][21] This is currently the subject of further investigation by our group.…”
Section: Discussionmentioning
confidence: 99%
“…While supine imaging may produce more optimal lumbar spine parameters, the reverse may be the case in the thoracic spine. Lovecchio et al, 10 using supine imaging, caution that proximal fusion constructs incorporating a flexible thoracic spine risk the creation of a "flattened" thoracic spine and truncated thoracic kyphosis, which has been shown to contribute to PJK. 21,30,31 Our stepwise linear regression of the normative alignment measurements of healthy volunteers found that while distal lumbar alignment was negatively impacted by advancing age, proximal lumbar lordosis was related to pelvic incidence.…”
Section: Discussionmentioning
confidence: 99%
“…6 Considerations to this end include age-dependent correction of PI-LL mismatch, 7,8 judicious use of osteotomies in "stiff spines," 9 and accounting for the patient's intrinsic ability to use thoracic kyphosis to compensate for residual malalignment above the upper instrumented vertebra (UIV). 10,11 Standing radiographs are representative of the multifactorial character of sagittal malalignment, which includes impaired muscle strength, 12,13 axial loading, and compensatory mechanisms within the axial and appendicular anatomy. 14,15 Barrey et al 16 proposed a multistep process for identifying and accounting for compensatory mechanisms in patients with ASD, which include changes in lumbar lordosis/ thoracic kyphosis, the presence of translational pathology such as retrolisthesis, and compensation through the appendicular anatomy such as knee flexion and ankle extension.…”
Section: Introductionmentioning
confidence: 99%